A contribution to knowledge of the development of marine life during the Permian and Triassic through the analysis of life histories of genera - Reguant, Salvador (Journal of Iberian Geology, 2007)
Data recently published on the longevity of various marine animal genera permits in-depht study of the history of marine life. The Permo-Triassic boundary, as well as the Permian and Triassic periods themselves, constitute a particularly interesting point in the history of life in the Phanerozoic, in that they straddle the most extensive extinction ever recorded.The analysis of the development of abundant genera (using classes and orders) in 13 marine animal taxa reveals that, on the one hand, all the taxa studied suffered the biggest change in their generic composition during these two periods precisely at the Permo-Triassic boundary, and, on the other hand, that certain groups display patterns during these two periods that do not conform to the overall trend.